Use of polymer modified mortar in controlling cracks in reinforced concrete beams - Ahmad, S.; Elahi, A.; Barbhuiya, Salim; Farid, Y. (Elsevier BV, 2012)
This paper presents the results of an experimental investigation on the strengthening of existing cracked RC members. The proposed technique consists of applying locally available polymer modified mortar in cracked beams to increase the load carrying capacity. A total of six full scale RC beams were constructed with the same material using the same mix and water-cement ratio. Initially, beams were tested until the development of cracks with width reached a limiting value of 1 mm. The beams were then repaired with the application of polymer modified mortar technique. After 3 days of water curing the beams were tested again and loaded till the failure. An improvement in the load carrying capacity was observed in the beams after the retrofitting. Results clearly demonstrate the effectiveness of the proposed technique in repairing the RC members for strengthening the existing structures.